A Rare Case of Serous Cystadenoma Ovary with Cholesterol Granuloma in an Adult Female - Murad Ahmed; Surabhi Gautam; Veena Maheshwari (International Journal of Toxins and Toxics, 2024)
In reaction to cholesterol crystals and foreign body giant cells, cholesterol granulomas are formed. These are the results of long-term inflammation brought on by the buildup of cholesterol crystals in tissues. The middle ear and paranasal sinuses are the most often reported locales; however, the mediastinum, breast, and ovary have all been implicated in a small number of cases. Here, we report a rare instance of an accidental ovarian cholesterol granuloma in an adult woman who had a right adenexal mass. Because of the fibrosis and adhesions, this tumor is occasionally mistakenly identified as ovarian cancer. The presence of cholesterol crystals and foreign body giant cells, which define cholesterol granulomas, usually results from persistent inflammation brought on by cholesterol crystal deposition in different tissues. Although the middle ear and paranasal sinuses are the most commonly reported locations for these granulomas, there have been a few uncommon cases where they have been found in unusual places such the mediastinum, breast, and ovary. In this report, we describe a unique case of an adult lady who came with a right adnexal tumor and an accidental cholesterol granuloma in her ovary. Due to the development of fibrosis and adhesions, the rare occurrence of cholesterol granulomas in the ovary complicates diagnosis because of the possibility that they are ovarian cancer. This example emphasizes how crucial it is to rule out cholesterol granulomas when making ovarian mass differential diagnoses, particularly in cases where fibrotic lesions are not expected. Misdiagnosis can result in needless invasive surgeries or cancer therapies
Keywords: Cholesterol granuloma; Chronic inflammation; Ovarian mass; Ovary. Cholesterol granuloma